The Mediating Role of Digital Financial Literacy : Examining How Problem Based Learning Influences Consumption Decision Making Among Adolescents - Gumilar, Desy Wulan Ayuning; Sangka, Khresna Bayu; Totalia, Salman Alfarisy (LPPM Universitas Pendidikan Mandalika, 2024)
This study aims to analyze the role of digital financial literacy in mediating problem-based learning in adolescents' consumption decision-making. The research method used a survey with a quantitative approach. The population consists of tenth-grade high school students, sampled using purposive sampling from classes that had undergone problem-based learning in economics subjects covering (1) consumption and (2) financial literacy and prioritizing scales, resulting in 142 respondents. The instrument in this study was a questionnaire on Google Forms, which wasÂ distributed via QR code. The data was analyzed using SPSS 25. The results obtained by digital financial literacy can significantly mediate problem-based learning in adolescent consumption decision-making with a Z value of 3.003 > 1.96 and sig 0.002 < 0.05. Integrating digital financial literacy in problem-based learning can synergize to improve students' critical thinking, which gives them the ability to make smart consumption decisions regarding their consumption activities.